Asuhan Keperawatan Pada Ny. K Keluarga Tn. W Dengan Gangguan Sistem Muskuloskeletal: Rheumatoid Arthritis Di Desa Karang Jati Kecamatan Tonjong Kabupaten Brebes - Khariri; Lina Farikha (STIKES Columbia Asia Medan, 2026)
Background: Non-communicable diseases (NCDs) are diseases caused by changes in human organs or degenerative diseases (age factor). Rheumatoid arthritis is a chronic autoimmune disease that occurs when the body's immune system mistakenly attacks joint tissues. According to WHO 2025, rheumatoid arthritis sufferers reach 355 million people worldwide. Method: This scientific paper uses a descriptive narrative method, namely by providing an overview of family nursing care to patients through a nursing process approach. The general objective of this paper is to understand and apply family nursing care to patients with Musculoskeletal System Disorders: Rheumatoid Arthritis. Results: Nursing diagnoses that appear in patients with Musculoskeletal System Disorders: Rheumatoid Arthritis include chronic pain and knowledge deficit. Conclusion: After nursing implementation for 2 days, the chronic pain diagnosis was partially resolved and the knowledge deficit was resolved, so the author performed routine discharge planning by doing warm compresses using ginger.